Networking in Black: Africana Culture in the Web 2.0 Age - Rice-Soley, Bessie
This study explores the ways in which Africana culture is articulated and reinforced on the Afrocentric social media site (SMS), Palavahut.com, as well as on popular sites such as YouTube, Facebook, and Twitter. It examines the characteristics and the extent to which users of such social networks affect culture when using this medium and how the present culture of social interaction in cyberspace influences cultural performance and ritual. I discuss how participation on such sites addresses and creates components of a Black Agenda for the Africana World. A mixed method approach is employed that includes content analysis, thematic analysis, and participant observation to analyze culture-specific activity within the sites' videos and blogs. Conventional wisdom is expressed by some scholars that globalization engenders cultural homogeneity and that different cultural groups worldwide embrace this uniformity. This loss of cultural distinction, however, is contrasted with indications that suggest a deep commitment to the retention of traditional culture and heritage. The larger implications of the study are that networks formed through SMS function as environments in which Africana cultures can flourish. In turn, these cyber communities serve as safe havens for communities historically marginalized by society.